2003
DOI: 10.1038/oby.2003.222
|View full text |Cite
|
Sign up to set email alerts
|

Are Current Health Behavioral Change Models Helpful in Guiding Prevention of Weight Gain Efforts?

Abstract: Effective procedures are needed to prevent the substantial increases in adiposity that have been occurring among children and adults. Behavioral change may occur as a result of changes in variables that mediate interventions. These mediating variables have typically come from the theories or models used to understand behavior. Seven categories of theories and models are reviewed to define the concepts and to identify the motivational mechanism(s), the resources that a person needs for change, the processes by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
551
0
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(580 citation statements)
references
References 163 publications
19
551
0
10
Order By: Relevance
“…Rothschild's MOA framework (11) encompasses the heterogeneity in determinants by stressing the significance of both individual-level and environmental influences on behaviour. The MOA framework integrates the core concepts of the Theory of Planned Behaviour and Social Ecological Models, which in combination have been identified as the most promising models for obesity prevention (41) .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Rothschild's MOA framework (11) encompasses the heterogeneity in determinants by stressing the significance of both individual-level and environmental influences on behaviour. The MOA framework integrates the core concepts of the Theory of Planned Behaviour and Social Ecological Models, which in combination have been identified as the most promising models for obesity prevention (41) .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Rothschild's MOA framework (11) encompasses the heterogeneity in determinants by stressing the significance of both individual-level and environmental Heterogeneity in barriers for snack choices 1585 influences on behaviour. The MOA framework integrates the core concepts of the Theory of Planned Behaviour and Social Ecological Models, which in combination have been identified as the most promising models for obesity prevention (41) . Applied to the food-choice context, the framework theorizes that when motivation, opportunity and ability for a certain dietary behaviour are sufficiently present, people will likely execute the behaviour.…”
mentioning
confidence: 99%
“…Accurately perceiving oneself as overweight or obese is considered an important cue for action and change and has been linked to greater motivation to engage in healthy lifestyle behaviors. 14,15 Growing evidence suggests that actual weight and perception of weight status often do not coincide, and that deviations between actual and perceived weight status are more common among overweight and obese individuals. [16][17][18][19] Among overweight adults, 43% of men and 18% of women perceived themselves to be of 'healthy weight or underweight'.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A recent review of theoretical health behaviour models concluded that little is known about the applicability of these models to the study of obesity prevention. 12 Many existing theories have been drawn from health psychology.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A recent review of theoretical health behaviour models concluded that little is known about the applicability of these models to the study of obesity prevention. 12 Many existing theories have been drawn from health psychology. Recently, these theories have been criticized for their exclusive or primary focus on psychological influences, without considering the sociocultural and environmental contexts in which behaviours occur.…”
Section: Introductionmentioning
confidence: 99%